2022
DOI: 10.3389/fnut.2022.999156
|View full text |Cite
|
Sign up to set email alerts
|

Timed restricted feeding cycles drive daily rhythms in female rats maintained in constant light but only partially restore the estrous cycle

Abstract: Light at night is an emergent problem for modern society. Rodents exposed to light at night develop a loss of circadian rhythms, which leads to increased adiposity, altered immune response, and increased growth of tumors. In female rats, constant light (LL) eliminates the estrous cycle leading to a state of persistent estrus. The suprachiasmatic nucleus (SCN) drives circadian rhythms, and it interacts with the neuroendocrine network necessary for reproductive function. Timed restricted feeding (RF) exerts a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Circadian disruption is associated with reproductive problems in humans [78] and animal models. [25,79] Schwartz in 1982 reported that bright light at night induced persistent estrus in female rats. [80] The SCN communicates to the MnPo to regulate the release of gonadotropin-releasing hormone and initiate the reproductive cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Circadian disruption is associated with reproductive problems in humans [78] and animal models. [25,79] Schwartz in 1982 reported that bright light at night induced persistent estrus in female rats. [80] The SCN communicates to the MnPo to regulate the release of gonadotropin-releasing hormone and initiate the reproductive cycle.…”
Section: Discussionmentioning
confidence: 99%